2019
DOI: 10.1002/cam4.1941
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and amino acid sequence polymorphism in Helicobacter pylori CagL hypervariable motif and its association with virulence markers and gastroduodenal diseases

Abstract: Genetic variability in cagL gene especially within the Helicobacter pylori CagL hypervariable motif (CagLHM) may affect the development of gastric cancer. Therefore, this study was conducted to investigate the association of CagL diversity with clinical outcomes and with H pylori virulence markers. A total of 126 patients with different gastric diseases including non‐ulcer dyspepsia (NUD), peptic ulcer disease (PUD), gastric erosion (GE), and gastric cancer (GC) were enrolled. H pylori was cultured from gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 56 publications
1
35
1
Order By: Relevance
“…Ogawa et al discovered complete RGD motifs in CagL sequences were observed from all isolates, which possibly imply the importance of the RGD motif for CagL function [26]. A recent investigation on this topic was performed by Yadegar et al in Iran, in which almost 97% of H. pylori clinical strains contained cagL gene [29]. Furthermore, their ndings highlighted the importance of a common CagL hypervariable motif (CagLHM) such as NEIGQ along with multiple C-type EPIYA repeats, which was linked to PUD, GE, and GC with more severity compared to NUD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogawa et al discovered complete RGD motifs in CagL sequences were observed from all isolates, which possibly imply the importance of the RGD motif for CagL function [26]. A recent investigation on this topic was performed by Yadegar et al in Iran, in which almost 97% of H. pylori clinical strains contained cagL gene [29]. Furthermore, their ndings highlighted the importance of a common CagL hypervariable motif (CagLHM) such as NEIGQ along with multiple C-type EPIYA repeats, which was linked to PUD, GE, and GC with more severity compared to NUD.…”
Section: Discussionmentioning
confidence: 99%
“…The incubation was performed at 37°C for 3-7 days under a microaerophilic atmosphere (5% O 2 , 10% CO 2 and 85% N 2 ) in a CO 2 incubator (Innova ® CO-170; New Brunswick Scienti c, USA). The suspected colonies were identi ed as H. pylori based on colony morphology, Gram staining, positive reaction for oxidase, catalase and urease tests, and also by H. pylori gene-speci c PCR following the previously described protocols [28,29]. Pure cultures from con rmed isolates were kept in 0.5 ml of Brain heart infusion (BHI) medium (Merck, Germany) containing 15% glycerol plus 20% FCS, and stored at -80°C until further analysis.…”
Section: H Pylori Culture and Identi Cationmentioning
confidence: 99%
“…In a study, particular polymorphisms upstream of the RGD motif at amino acid residues 58–62, called the CagL hypervariable motif (CagLHM), were correlated with severe disease progression in a geographically dependent manner [ 51 , 52 ]. Recently, studies have also found CagL polymorphisms such as D58, K59, M60, E62, K122, and I134 and novel CagL variants, and shown their association with chronic gastritis and PUD [ 53 , 54 ].…”
Section: Caga Translocationmentioning
confidence: 99%
“…The integrity of cag-PAI was evaluated by determining the presence of several gene clusters within the cag-PAI region. The presence or absence of selected gene clusters was defined as an intact cag-PAI, a partially deleted cag-PAI, or complete absence of cag-PAI [26]. The complete absence of cag-PAI was confirmed by a PCR assay of cag-PAI empty site [26].…”
Section: Determination Of Gene Clusters Within Cag-pai and Caga Sequementioning
confidence: 99%